Splenopancreatic ductal adenocarcinoma with multiorgan metastasis in a northern water snake (Nerodia sipedon) - Matthews, Mary Ellen; Eshar, David N.; Delk, Katie W.; Pohlman, Lisa M.; Andrews, Gordon A. (My University, 2014)
A 16-yr-old northern water snake (Nerodia sipedon) presented with a large, firm midcoelomic swelling. A complete blood count, survey radiographs, coelomic ultrasound, and fine needle aspirate of the mass were performed. Survey radiographs revealed a soft tissue opacity mass. Ultrasonographic examination confirmed the presence of the mass but could not aid in its visceral localization. After 2 weeks, the snake presented again because of continued anorexia and poor quality of life. Euthanasia was performed. Gross necropsy revealed a multilobulated mass attached to and effacing the splenopancreas. Histologically, the mass was composed of cuboidal to columnar neoplastic epithelial cells forming tubules surrounded by variable amounts of fibrovascular stroma. Histological examination and immunohistochemical staining of other tissues revealed local invasion in the subserosa and tunica muscularis of the stomach, metastasis within the liver, in the mesovarium, and an intravascular metastasis within the ventricle of the heart surrounded by a thrombus.
Keywords: Ductal adenocarcinoma; Immunohistochemistry; Nerodia sipedon; Northern water snake; Splenopancreas